STUDENTS’ PERCEPTION ON VIDEO MAKING TASK TOWARDS THEIR SPEAKING SKILL - Nurhasanah; Salasiah; Sianna (La Parole : Journal of Language Teaching and Pedagogy, 2019)
The aimed of this study was to knowing students' perceptions about the task of making videos on English speaking skills of English department of Universitas Muhammadiyah Parepare. This study also aims at how the effect of using video making tasks on students' speaking skills. And this research is expected to increase knowledge and information in the teaching and learning process. To improve students' speaking understanding, researchers used qualitative research methods. The subjects in this study were the 8th of English department of Universitas Muhammadiyah Parepare in the force 2016, totaling 10 people. In addition, data was collected through interviews. The results showed that students generally liked the video making task and could improve their speaking skills. The task of making this video is to develop speaking components such as vocabulary, pronunciation, and fluency in speaking. Researchers also found several advantages of the video making task from student perceptions, namely: making students able to use technology, increasing creativity, increasing self-confidence, and making students challenged to deepen language.